2000
DOI: 10.1117/12.411730
|View full text |Cite
|
Sign up to set email alerts
|

<title>Static and dynamic testing of bridges and highways using long-gage fiber Bragg grating based strain sensors</title>

Abstract: Fiber optic Bragg gratings packaged in long gage configurations are being used to measure static and dynamic strain in structures and structural models to monitor structural health and predict damage incurred from a seismic event. These long gage sensors are being used to experimentally verify analytical models of post-earthquake evaluation based on system identification analysis. This fiber optic deformation measurement system could play a significant role in monitoring/recording with a higher level of comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…The fourier spectral lines of the measured data are in very good agreement with the theoretically predicted values of Tab. 1 . In general, it is observed that in the x-plane of the prism at FBG3 only a minimum of dynamic strain response occurs, whereas the highest strain levels are detected in the z-direction at FBG1.…”
Section: Resultsmentioning
confidence: 95%
“…The fourier spectral lines of the measured data are in very good agreement with the theoretically predicted values of Tab. 1 . In general, it is observed that in the x-plane of the prism at FBG3 only a minimum of dynamic strain response occurs, whereas the highest strain levels are detected in the z-direction at FBG1.…”
Section: Resultsmentioning
confidence: 95%
“…On the other hand, a LPBG presents no reflected band and behaves as a band-stop filter in transmission [17,19], as a result of the coupling between the forward propagating and cladding modes of the fiber. The fact that the optical properties of gratings are affected by temperature variations and/or mechanical deformations makes them an important and useful sensor [20,21], which can be applied in different areas, such as biomechanics [22], civil engineering, [23] and aeronautics [24,25]. The same working principle of gratings, when used in coax cables, presents many advantages, mainly when the final application is devoted to the continuous monitoring of buildings, bridges and other civil engineering constructions.…”
Section: Bragg Grating and Long Period Bragg Gratingmentioning
confidence: 99%
“…Extensive literature on recent development of optic FBG distributed strain sensors, and their applications in structural health monitoring of civil infrastructure systems can be found in [6] and [7] . Schulz et al [8] report the use long gauge length FBG sensor optimized for a sampling frequency of 1 kHz for long-term monitoring of two RC bridges. More recently, the authors' laboratory has committed special effort towards developing a feasible distributed long-gage strain sensing system for practical adaptation to civil structural engineering [9] .…”
Section: Introductionmentioning
confidence: 99%